An Overview on Bioeconomy in Agricultural Sector, Biomass Production, Recycling Methods, and Circular Economy Considerations - Toplicean, Ioana-Maria; Datcu, Adina-Daniela (Agriculture (Basel), 2024)
This review examines the essential components of a circular economy (CE) in relation to the agricultural sector. The bioeconomy and circular economy are crucial for sustainable global industrial growth, focusing on closed-loop systems. The sustainability debate centers on intergenerational equity and natural capital. The CE requires new environmental technologies and global coordination in order to combat climate change and biodiversity loss. In addition, efficient food production and waste reduction are essential due to population growth. However, biomass is vital for a bio-based economy, impacting food waste and climate change. Grasslands support sustainable dairy production and carbon sequestration. Thus, effective waste and wastewater management are critical, with biomass energy providing renewable alternatives. Nonetheless, biofuels remain key for sustainability, focusing on pollution control and Green Chemistry. It is well known that sustainable transportation relies on bioenergy, with ongoing research improving processes and discovering new fuels. One notable challenge is managing heavy metals in biofuel production, and this underscores the need for eco-friendly energy solutions. The main purpose for this review paper is to create a connection between circular economy aspects and the agricultural system, with focus on the following: bioeconomy research, biomass utilities, and biofuel production. Extensive research was performed on the specialized literature by putting in common the main problems. Key subjects in this paper include the use of biomass in agriculture, the problems of plastic recycling, and the function of the CE in mitigating climate change and biodiversity loss. Efficient food production and waste minimization are highlighted due to their relevance in a growing population. The study’s detailed research and discussion aim to give important insights into how these practices might promote economic development and sustainability. Furthermore, the study covers important waste management issues such as food waste, plant composting, and chemical waste neutralization. These topics are critical to understanding the circular economy’s broader implications for minimizing environmental damage and implementing sustainable waste management strategies.